2003
DOI: 10.1093/emboj/cdg280
|View full text |Cite
|
Sign up to set email alerts
|

Ras-GRF1 signaling is required for normal  -cell development and glucose homeostasis

Abstract: Development of diabetes generally re¯ects an inadequate mass of insulin-producing b-cells. b-cell proliferation and differentiation are regulated by a variety of growth factors and hormones, including insulin-like growth factor I (IGF-I). GRF1 is a Rasguanine nucleotide exchange factor known previously for its restricted expression in brain and its role in learning and memory. Here we demonstrate that GRF1 is also expressed in pancreatic islets. Interestingly, our GRF1-de®cient mice exhibit reduced body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
10

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 47 publications
6
76
0
10
Order By: Relevance
“…Initially described as having restricted expression in postnatal mice brain (21), Rasgrf1 expression has been reported in adult pancreatic islets as well (12). To determine whether and at which developmental stage Zac1 and Rasgrf1 are coexpressed, we analyzed their expression pattern in fetal, perinatal, and early adult mice pancreata.…”
Section: Resultsmentioning
confidence: 99%
“…Initially described as having restricted expression in postnatal mice brain (21), Rasgrf1 expression has been reported in adult pancreatic islets as well (12). To determine whether and at which developmental stage Zac1 and Rasgrf1 are coexpressed, we analyzed their expression pattern in fetal, perinatal, and early adult mice pancreata.…”
Section: Resultsmentioning
confidence: 99%
“…GRF1-KO, GRF2-KO and GRF1/2-DKO mice were generated as described (Fernández-Medarde et al, 2002;Font de Mora et al, 2003). WT controls and knockout mice were maintained in a C57BL/6 background and kept on a 12 h light:12 h dark cycle.…”
Section: Animalsmentioning
confidence: 99%
“…Because of their high structural homology and similar expression patterns, the specific functional properties of the two isoforms within this mammalian GEF family are not fully defined (Feig, 2011;Fernández-Medarde and Santos, 2011). Previous characterization of GRF1-knockout (KO) mice has documented a specific implication of this protein in memory formation (Brambilla et al, 1997;Giese et al, 2001), postnatal growth (Itier et al, 1998;Fernández-Medarde et al, 2002), pancreatic β-cell function and glucose homeostasis (Font de Mora et al, 2003;Manyes et al, 2014), and neurosensory processes and photoreception (Fernández-Medarde et al, 2007Hysi et al, 2010). By contrast, the study of Rasgrf2-null animals has demonstrated that GRF2 and GRF1 are not functionally overlapping regarding memory formation or body growth (Fernández-Medarde et al, 2002;Jin et al, 2013;Li et al, 2006) and has also documented that GRF2 plays specific functional roles in control of T-cell proliferation and signaling in lymphocyte proliferation, T-cell signaling responses and lymphomagenesis (Ruiz et al, 2007(Ruiz et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that Ras signaling is required for ␤-cell growth and participates in the response of pancreatic ␤-cells to prolactin during pregnancy (Amaral et al 2003(Amaral et al , 2004. In addition, targeted disruption of the Ras activator RasGRF1 results in reduced ␤-cell proliferation and decreased ␤-cell mass (Font de Mora et al 2003). When activated, Ras initiates a signal transduction cascade that culminates with the phosphorylation and activation of ERK1 and ERK2.…”
Section: Ras/erk Signaling Is Down-regulated In Hnf-4␣-deficient ␤-Cellsmentioning
confidence: 99%
“…Many hormones and cytokines control the growth of the endocrine pancreas. The importance of the Ras/MAP (mitogen-activated protein) kinase signaling cascade in mediating the response to these growth factors and hormones in ␤-cells has been demonstrated by targeted disruption of a Ras guanine exchange factor, RasGRF1, which leads to a reduction in ␤-cell proliferation and ␤-cell mass (Font de Mora et al 2003). In addition, activated ERK1/2 has also been suggested to mediate the ␤-cell response to pregnancy hormones (Amaral et al 2003(Amaral et al , 2004.…”
Section: Ras/erk Signaling In the ␤-Cell Is Dependent On Hnf-4␣mentioning
confidence: 99%